EFFECT OF TAJIKISTAN ALUMINUM PLANT WASTE ON CATTLE ORGANISMS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The article reveals the negative impact of emissions from the Tajik aluminum plant on the general indicators of cattle blood based on the conducted experiments. It was established that fluorinated intoxication in the body under the influence of industrial emissions, that is, provoking the development of fluorosis, is manifested by disturbances in the enzyme system, mineral, carbohydrate, protein metabolism, as well as in the liver.